Implementasi Software Cx-Designer Sebagai Media Pembelajaran Pada Mata Pelajaran Pemrograman Sistem Kontrol Mekanik - Gumelar, Ramdan (2015)
Skripsi with the title "Implementation of Cx-Designer Software For Learning Media in Subject Mechanical Control System Programming" an experimental study conducted in class XII student competency skills Mechanical Controls in SMK Negeri 1 Cimahi 2014/2015 school year. This study was conducted to determine differences in student learning outcomes in the cognitive who use Cx-Designer software with students without using Cx-Designer software for learning media in subject mechanical control system programming. The method used is a quasi experimental design. Research done by giving two unequal treatment of the two groups of students. First, get a teaching experimental group using Cx-Designer software as a learning medium. Second, control group getting teaching without using Cx-Designer software as a learning medium. Data was collected through a multiple choice test instrument given to students at the beginning and end of the study, thus be seen how different learning outcomes between the two groups. The results showed that there are differences in student learning outcomes in the cognitive domain. It is known from the average grade posttest experimental values greater than the average value posttest control class. In addition, in terms of improvement of learning outcomes (gain) students, the average value of the gain between the experimental class is greater than the control class.